Oral Presentations 2019
DOI: 10.1136/jech-2019-ssmabstracts.100
|View full text |Cite
|
Sign up to set email alerts
|

OP111 Oral health, disability and physical function: results from studies of older people in the UK and USA

Abstract: Results In all the three countries, this study finds health expenditure to be the predominant out of pocket cost incurred by women experiencing violence. Women who experience violence also have statistically significant higher depression, disability and acute illness scores, and thus indicate the broader health impacts of VAWG. These health impacts affect the overall productivity of women experiencing violence. Approximately 80 million productivity work days in Pakistan, 65 million productivity work days in Gh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Levels of D-dimer, the main prognostic of coagulopathy, increase naturally with age, hence the D-dimer test has a high false positive rate in elderly patients. Why D-dimer increases with age is not known but it likely reflects a higher level of vascular inflammation [46]. In cytokine storms, high levels of IL-6 cause vascular endothelial cells to secrete fibrin, which causes small clots to form in the microvasculature of the body.…”
Section: Increased Inflammation and Cytokine Storms In The Agedmentioning
confidence: 99%
“…Levels of D-dimer, the main prognostic of coagulopathy, increase naturally with age, hence the D-dimer test has a high false positive rate in elderly patients. Why D-dimer increases with age is not known but it likely reflects a higher level of vascular inflammation [46]. In cytokine storms, high levels of IL-6 cause vascular endothelial cells to secrete fibrin, which causes small clots to form in the microvasculature of the body.…”
Section: Increased Inflammation and Cytokine Storms In The Agedmentioning
confidence: 99%
“…Oral health, enabling natural eating, speaking, smiling, and socializing, plays a vital role in overall health (5,6). Deterioration of oral health can lead to various adverse health outcomes, such as cardiovascular diseases (7), cognitive impairment (8), disability (9), and all-cause mortality (10). However, studies have suggested that dental diseases could be prevented and reversed (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In China, the percentage of people in China aged 60 years or over is rising dramatically [1]; persons of increasing age are more likely to suffer from various oral problems [2]. At present, though a certain proportion of oral mucosal diseases (OMD) does not need active treatment, but there is some evidence that people with oral diseases are associated with various negative outcomes, such as poor quality of life, a heavy global burden on social and economic health, high risk of disability, and impaired physical function [3,4], particular in the elderly [5,6].…”
Section: Introductionmentioning
confidence: 99%